Immunohistochemical features of the portal tract mononuclear cell infiltrate in chronic aggressive hepatitis. Issue 12 (December 1992) - Senaldi, G; Portmann, B; Mowat, A P; Mieli-Vergani, G; Vergani, D
Abstract : The portal tract mononuclear cell infiltrate has been characterised in 28 liver biopsy samples showing features of chronic aggressive hepatitis from 12 patients with autoimmune chronic active hepatitis, 12 with primary sclerosing cholangitis, and four with other chronic liver diseases (two with alpha 1-antitrypsin deficiency, one with Wilson's disease, and one with chronic hepatitis B infection). In all patients liver disease had started in childhood. The mononuclear cell infiltrate was investigated by a two step immunoperoxidase technique using monoclonal antibodies to: total, alpha/beta T cell receptor positive, helper/inducer, suppressor/cytotoxic T lymphocytes; B lymphocytes; killer/natural killer cells; monocyte/macrophages; and to the activation markers HLA-DR antigens, interleukin 2 receptor (IL-2R), transferrin receptor, and 4F2Ag. In all samples the infiltrate consisted of mainly alpha/beta T cell receptor T lymphocytes. Although T helper/inducer cells predominated in patients with autoimmune chronic active hepatitis, T suppressor/cytotoxic lymphocytes were preponderant in patients with primary sclerosing cholangitis and the other chronic liver diseases. Killer/natural killer cells accounted for up to 25% of the mononuclear cell infiltrate in patients with autoimmune chronic active hepatitis, being rare or absent in the other diseases. Monocytes/macrophages were always found, but they were more numerous in primary sclerosing cholangitis than in the other chronic liver diseases. B lymphocytes were rare or absent in all subjects. Activated mononuclear cells were present in all subjects, but although in patients with autoimmune chronic active hepatitis and primary sclerosing cholangitis most cells of the infiltrate expressed HLA-DR antigens and up to 75% IL-2R, in other forms of chronic liver diseases HLA-DR positive cells were less common and IL-2R positive cells ere rare or absent. These results show that the cells responsible for the histological characteristics of chronic aggressive hepatitis vary in their functional phenotype and state of activation according to the type of underlying liver disorder, confirming the involvement of different pathogenetic mechanisms.